Organ Index, Toxicological, and Bioaccumulation Study of Sub chronic Intraperitoneal Injected Silver Nanoparticles in Albino Mice Males - Sarab Mohammed M. Razooki (Journal of Global Pharma Technology, 2019)
To investigate the sub chronic toxicity effects of intraperitoneal injected silver nanoparticles (Ag NPs) (24.52 nm), Albino mice males repeatedly exposed to three different doses (12.5, 25, and 50 mg/kg) of Ag NPs for 4 weeks. The accumulations of injected doses in different organs were evaluated. The results showed a significant changes in organs indexes with a good relations to the histopathological effects were noted which ranges between infiltration of inflammatory cells to coagulative necrosis in liver, multiple hemorrhage and cast forming in kidney, and amyloid deposition in spleen, thickening of intestinal villi, and sever interstitial broncho pneumonia as adverse effects in studied organs with dose related manner. Significant changes in hematological and biochemical parameters were detected combined with a considerable increasing in antioxidant enzymes in a dose dependent manner. The reduction in thyroid hormones levels T3, T4, and thyroid stimulating hormone (TSH). The highest accumulated Ag means values were recorded in liver, spleen, lung, and kidney respectively followed by brain, heart, small intestine, and testes in the order with dose depended manner which express the toxicological effects were recorded.Keywords: Ag NPs, Accumulation, Organ index, Biochemical parameters, Histopathology.